1979
DOI: 10.1002/kin.550111205
|View full text |Cite
|
Sign up to set email alerts
|

Addition of trichloromethyl radicals to tetrachloroethylene

Abstract: Abstract'The gamma-radiation-induced free-radical chain reactions in liquid CC14-C&L-c-CsHly mixtures were studied in the temperature range of 363-448°K. T h e main products in this system are chloroform, hexachloropropene and chlorocyclohexane. These products are formed via reactions (1)- (5): (1) From this result and the previously determined Arrhenius parameters of reaction ( l ) , ti? is I'iiund t o he given by log k ? (l/mol-sec) = 7.58 -9.?9//1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1980
1980
1980
1980

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…In a recent study of the 3130-A photolysis of CH20 at 25"C, we have found that $1 and $2 can be determined relatively simply using isobutene as an H-atom scavenger [19]. We have applied this technique in the present study to provide seemingly reliable new estimates of $1 and $2 at selected wavelengths from 2890 to 3380 A.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a recent study of the 3130-A photolysis of CH20 at 25"C, we have found that $1 and $2 can be determined relatively simply using isobutene as an H-atom scavenger [19]. We have applied this technique in the present study to provide seemingly reliable new estimates of $1 and $2 at selected wavelengths from 2890 to 3380 A.…”
Section: Introductionmentioning
confidence: 84%
“…The experimental setup and the method of gas chromatographic analysis were the same as that used in the previous work [19]. In order to isolate the different wavelengths from the high-pressure mercury arc (Osram HBO 500 W), we used a high-intensity grating monochromator (Schoeffel GM 250).…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting feature of these data is the regular enhancement of the quenching rate constant for the L state with excitation at the longer wavelengths; k4(2662)/k4(3130) is approximately constant, independent of the nature of the quenching gas. This effect has been inferred from less direct measurements of k4/k& by Mettee [33] and Horowitz and Calvert [34] from steady-state fluorescence studies. The effectiveness of the L state quenchers appears to be related to the polarizability of the molecules as suggested in other studies of excited SO2 singlet and triplet quenching [33-381. Presumably the excited SO2 molecule acts as an electrophilic reactant on collision with a polarizable molecule to form a highly polarized charge-transfer complex which may enhance intersystem crossing or internal conversion of the excited SO2 species.…”
Section: Quenching Of the S And L States By Some Atmospheric Gasesmentioning
confidence: 93%
“…From the kinetic mechanisms I1 and I11 presented, we would expect eqs. (33) and (34) to describe the ratio of the intensities for the steady-state condition (Zs/I&: (33) Using eqs. (33) and (34) and the appropriate kinetic data which we obtained from the fitting of the Zso/ILo-pressure data and the Stern-Volmer quenching constants we simulated the conditions employed by Shaw and coworkers.…”
mentioning
confidence: 99%
See 1 more Smart Citation